2018
DOI: 10.1002/glia.23460
|View full text |Cite
|
Sign up to set email alerts
|

Microglia have a more extensive and divergent response to interferon‐α compared with astrocytes

Abstract: Type I interferons (IFN-I) are crucial for effective antimicrobial defense in the central nervous system (CNS) but also can cause severe neurological disease (termed cerebral interferonopathy) as exemplified by Aicardi-Goutières Syndrome. In the CNS, microglia and astrocytes have essential roles in host responses to infection and injury, with both cell types responding to IFN-I. While the IFN-I signaling pathways are the same in astrocytes and microglia, the extent to which the IFN-I responses of these cells d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 72 publications
(115 reference statements)
3
37
0
Order By: Relevance
“…Additionally, the transcriptome of microglia from 564Igi mice is largely defined by a response to IFN‐I, with a significant portion of IFN‐I‐dependent genes enriched in processes such as IFN‐I production, environmental sensing, and phagocytosis (Bialas et al, ). Of note, these functional properties are similar to those recently identified in IFN‐α‐treated microglia (Li et al, ). It has also recently been demonstrated that microglia mediate pathologic dendritic pruning of hippocampal neurons in an anti‐DNA antibody‐mediated mouse model of CNS lupus (Nestor et al, ).…”
Section: The Response Of Microglia In Il‐6‐ and Ifn‐i‐mediated Neuroisupporting
confidence: 84%
See 4 more Smart Citations
“…Additionally, the transcriptome of microglia from 564Igi mice is largely defined by a response to IFN‐I, with a significant portion of IFN‐I‐dependent genes enriched in processes such as IFN‐I production, environmental sensing, and phagocytosis (Bialas et al, ). Of note, these functional properties are similar to those recently identified in IFN‐α‐treated microglia (Li et al, ). It has also recently been demonstrated that microglia mediate pathologic dendritic pruning of hippocampal neurons in an anti‐DNA antibody‐mediated mouse model of CNS lupus (Nestor et al, ).…”
Section: The Response Of Microglia In Il‐6‐ and Ifn‐i‐mediated Neuroisupporting
confidence: 84%
“…Similarly, the expression of the IFN‐I receptor genes IFNAR1 and IFNAR2 is also widespread (Zhang et al, , ), enabling all cell types in the CNS of humans and mice to respond to IFN‐I. Interestingly, in vitro studies have shown that microglia have a more pronounced response compared with astrocytes and neurons, suggesting that microglia are the major IFN‐I responder cell population in the CNS (Li et al, ; Wang & Campbell, ).…”
Section: Production Signaling and Effects Of Il‐6 And Ifn‐i In The Cnsmentioning
confidence: 99%
See 3 more Smart Citations